ANALYZING STRATEGIES FOR STRENGTHENING LITERACY COMPETENCE AT THE JUNIOR HIGH SCHOOL LEVEL AMONG SCHOOL TEAMS AT THE DISTRICT AND CITY LEVELS IN INDONESIA - Deslana Roidja Hapsarini; Al-Amin; Cut Ita Erliana; Defi Irwansyah; Dahlan Abdullah (Indonesian Journal of Education (INJOE), 2023)
This study delved into the intricate realm of enhancing literacy competence at the junior high school level among school teams operating at the district and city levels in Indonesia. With a focus on collaborative efforts, this research analyzed various strategies to bolster literacy skills, comprehensively exploring the multifaceted challenges and potential solutions. The study examined the historical background and significance of literacy competence in Indonesia's junior high schools to grasp the context. It addressed the pressing problem of inadequate literacy skills among students and identified vital contributing factors, such as limited access to resources, linguistic diversity, and disparities in socioeconomic conditions. The study set forth four primary research objectives: (1) to assess the current literacy competence levels in junior high schools, (2) to uncover the internal and external factors influencing literacy development, (3) to scrutinize effective strategies and best practices for strengthening literacy skills within school teams, and (4) to formulate targeted recommendations for district and city-level policymakers, educators, and stakeholders, through a comprehensive investigation encompassing public and private schools across diverse regions, the research aimed to shed light on the complex interplay of factors shaping literacy outcomes. This study, despite its limitations in terms of time and resource constraints and personal influences, seeks to provide valuable insights to guide collaborative efforts to boost among junior high school students in Indonesia.